Georgia Architectural and Historic Properties Survey of Dickey St., Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Dickey St., Sycamore, Turner County, Ga., 1981. Bungalow style with addition. Gabled roof with exposed rafters and brackets. Gabled porch supported by square posts on brick (see photo). Shiplap siding. Double sash windows with 3/1 lights. Exterior chimney. On brick piers. Good condition. Date of Construction: c. 1925. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Dickey St., Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 52.3 MB (54,898,599 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)